Shuddering Attacks - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
The successful treatment of shuddering attacks with a beta-adrenergic blocker (propranolol) in a 3 year old girl is reported from the Division of Pediatric Neurology, Children's Hospital of Philadelphia, University of Pennsylvania, Philadelphia PA.